Ingerencja Turków osmańskich w sprawy wewnętrzne Bizancjum za panowania Murada I i Bajezyda I - Korczak, Rafał (Acta Universitatis Lodziensis. Folia Historica, 2005)
When in XIV to ages the Byzantine Empire had to level with the Ottomans, did not turn over to himself the matter that in the second half of this century it would become the vassal of his own eastern neighbour. An object of this article is the proof how far the Turks used their own superiority, to inform Byzantium his political not independence and to steer with the course of internal activities of the Constantinople mansion. Events about which the speech, happened on the monarch of John V Palaeologus (1354-1391) and the beginning of rule his son, Manuel II (1392-1425). The battle under Ankara broke this period of humiliations given to the Empire by two outstanding the Ottoman suvereigns: Murad I (1362-1389) and Bayezid (1389-1402). In 1372/1373 Byzantium became a vassal of Ottoman Turks. In 1373 in Adrianople and Constantinople exploded parallel mutinies. Andronicus Palaeologus and Saudji together went against to their own fathers. After strangling of the rebellion, mutineers were blinded from the order of Murad. Turks had a very precise cognition, when he is going for the dynastic conflict in Byzantium which used to the interference into internal matters of the Empire. The last Palaeologuses, perfidious in the face themselves, scrupulous in the face the Ottomans, administrated in Constantinople behind the consent Adrianopole, what placed them in the humiliating position. The authority is however so attractive honour that for her conquest were ready to tear family tieses, what sedulously used: first Murad I, promoting Andronicus IV against father to John V, and afterwards Bayezid, protecting John VII, being in opposition in the face his own grandfather of John V.